Islamic finance for climate action and sustainability - Adam Sa'ad, Auwal; Raja, Rehan; AbdulRazak, Abdulhadi; Qazi Muhammad, Adnan Hye (Springer, 2025)
The public report of the Intergovernmental Panel on Climate Change signals an alarm about the drastic environmental changes, which specify that without immediate climate actions, numerous parts of Asia, specifically Pacific Asia, may vanish in the forthcoming three decades. ..